The Role of Humans in Creating a Smart City - Maspero Situngkir (JOURNAL of LEGAL RESEARCH, 2021)
Every human being is born unique with their own talents and abilities. Therefore, every human being is unique. We cannot compare humans because every human being has its own weaknesses and weaknesses. Thus humans are social creatures who need each other to complement each other. If the talents and abilities that are owned can be channeled properly and correctly, it will create extraordinary innovations that can change mindsets and facilitate all human activities, including by creating Smart Home and Smart City. Of course, this cannot be separated from the development of science and technology in the current era of globalization. Thus, the role of the government is also expected to support this because it is an integrated system. Thus, to realize a smart city, it is necessary to have a system that is mutually integrated and supports each other, namely smart governance, smart society, smart life, smart economy, smart environment, and smart branding.